Data Linkage for Optimizing Rectal Cancer Care in Alberta - Le, Quynh; Shack, Lorraine; Elwi, Adam; Coutinho, Francesca; Rochon, Ryan; Mcmullen, Todd; Buie, Donald (International Journal of Population Data Science, 2018)
Introduction Despite good overall care in Alberta Health Services the local recurrence rates are higher than what is accepted as standard of care for rectal cancer treatment. There are variations in pre-operative staging, application of best surgical techniques and pathological grading, use of neoadjuvant and adjuvant therapies, and in clinical reporting. Objectives and Approach We aimed at reducing the variations through the design and implementation of a provincial clinical pathway for rectal cancer by 2018. Our approaches included: 1) multidisciplinary tumor board consultation together with physician education sessions in reviewing standards of care and quality metrics; 2) data linkage and analysis based on chart reviews and extraction of data from Alberta Cancer Registry; and 3) production of provincial reports and individual feedbacks to physicians. CancerControl Alberta and Cancer Strategic Clinical Network collaborated in the linkage and analysis of data as well as mobilization oncology physicians to the initiative. Results A review of a set of metrics for producing individual and provincial feedback reports to rectal cancer physicians. The set has 24 key quality metrics includes five, four, eight, and six metrics for radiologists, pathologists, oncologists, and surgeons respectively. Thirty-two surgeons have received individual physician feedback reports. Feedback reports for radiologist, pathologist and oncologist are being finalized with input from key opinion leaders in each physician group. Key impacts to the quality of rectal cancer diagnosis, treatment, and care between 2013 and 2015 include increases in use of rectal cancer pre-operative MRIs for curative resections (+23%), completeness of synoptic MRI reports for pre-operative MRIs (+21%), grade 3 TME of curative resections (+4%), and pathologic reporting of TME assessments (+2%). Conclusion/Implications Physician feedback report system will enable the Alberta rectal cancer community to sustain the results and address strategies to continuously enhance the quality of rectal cancer care and survival. We recommend ongoing annual dissemination of feedback reports to support continuous improvement of rectal cancer care.